(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
We cannot overstate the value of technology in the classroom, since it has made it easier for teachers to teach and for students to learn. The usage of technology has made teaching and learning more fun. One of the most significant advantages of e-learning is that it has the ability to make learning and teaching independent of time, location, and speed. The benefits that e-learning can provide It was possible to overcome traditional classroom constraints and construct an open, low-cost, contemporary, and technology-based virtual campus. As a result, new technological boundaries have emerged, which can be minimized by a thorough analysis of the design and technology used. Educators are in a unique position to create and implement innovative learning systems based on learning research, educational technology, and educational innovations.